The investigation of shape memory recovery loss in NiTi alloy - Ozkul, Iskender; Kalay, Ece; Canbay, Canan Aksu (Iop Publishing Ltd, 2019)
Shape memory effect is the most effectively performed on NiTi shape memory alloy. The shape memory effect phenomena are related to solid-state phase transformation so the atomic neighbourhood orientation keeps during the phase transformation process. Stress and energy release during the phase transformation have effects on orientations of the atomic structure. However, if SMAs are exposure to repeated regular deforming and shape recovery cyclings, this will eventually cause some loses in their shape memory recoverability. In this study, the shape memory effect loss ratio of Ni46.84Ti53.16 (at%) alloy was investigated by systematic stress-strain mechanical tests and significant shifts was recorded on shape recovery ratios.
Keywords: shape memory effect; recovery ratio; DSC; XRD